JIHAD ALA GERAKAN MAHASISWA PEMBEBASAN: SEBUAH CATATAN ATAS RADIKALISME DI KALANGAN MAHASISWA - Lufaefi, Lufaefi (Pascasarjana UIN ANTASARI Banjarmasin, 2018)
Jihad is often identified with violence. The destruction of objects that are claimed to be un-Islamic is frequently become the target of jihad by some Islamic groups. As a result, Islam is often accused of being a religion of violence and terrorism. GEMA Pembebasan is a Student movement that aspires to the establishment of Islamic State in Indonesia. The GEMA jihad model is fighting against the unbeliever. In this case, GEMA is not interpreted Jihad as a learning jihad, political jihad, economic jihad, and so on. The GEMA Liberation jihad model keeps the dark sides of radicalism that threaten the socio-cultural of Indonesia. GEMA Liberation Jihad impacts on the frequency of Islam being accused as a radical religion and terror. Jihad sering diidentifikasi sebagai tindakan kekerasan. Penghancuran benda-benda yang diklaim tidak islami juga tidak jarang menjadi sasaran jihad di jalan Allah oleh beberapa kelompok Islam. Akibatnya, Islam sering dituduh sebagai agama kekerasan dan terorisme. GEMA (Gerakan Mahasiswa) Pembebasan adalah gerakan mahasiswa yang bercita-cita untuk pembentukan Negara Islam di Indonesia. Model jihad GEMA ini hanya melawan kaum kafir. Jihad tidak diartikan sebagai jihad dalam menuntut ilmu, jihad dalam politik, jihad dalam ekonomi, dan sebagainya. Model jihad Pembebasan GEMA menyelamatkan sisi gelap radikalisme yang mengancam sosio-budaya Indonesia. Implikasi jihad Pembebasan GEMA berdampak pada frekuensi Islam dituduh sebagai agama dan teror radikal.